ANALYSIS GEOELECTRIC STRIKE DIRECTION OF MAGNETOTELLURIC SURVEY IN GEOTHERMAL AREA - Yogasatria, Galang
Magnetotelluric (MT) method plays an important role in geothermal exploration. For MT data interpretation, 2D modelling is still performed in a routine basis since 3D MT modelling is computationally intensive and needs sigificant computational resources. In 2D modelling, information on geoelectric strike directionality from MT impedance tensor is important. In this study, various approaches for geoelectric strike estimation have been performed on 180 MT sounding data from a geothermal prospect area. The results from phase tensor analysis and principal axis of impedance tensor, verified by tipper strike present that the dominant geoelectric strike of the study area is N300°E- N305°E. This result is in agreement with the regional structure of the study area. We also compare 2D models from inversion of MT data rotated to principal axis frequency by frequency and from MT data rotated to a dominant geoelectric strike. The results show that the ambiguity of principal axis needs to be reviewed since the RMS error of the inverse model is relatively high and reduced when the ambiguity was considered. Careful MT impedance tensor rotation should be performed to obtain data for 2D modelling. The subsurface resistivity model from both rotation are slightly different, yet they still show the geothermal system of study area.